Penerapan Strategi Pembelajaran Everyone is a Teacher Here (ETH) untuk Meningkatkan Kreativitas Belajar Fisika Siswa di Kelas XI SMA N 2 Tukka - Putri Ayu Handayani Telaumbanua; Herti Vioni; Yenni Khairani Lubis (Gravity Journal, 2026)
The background of this study was the low level of students’ learning creativity in Physics, particularly on the topic of Electromagnetic Waves, in Class XI-1 of SMA Negeri 2 Tukka. This condition was caused by the learning process being predominantly teacher-centered through the lecture method, resulting in students being less active in asking questions, expressing opinions, and participating in classroom activities. This study aimed to determine the improvement of students’ learning creativity after the implementation of the Everyone Is A Teacher Here (ETH) learning strategy on the topic of Electromagnetic Waves in Class XI-1 of SMA Negeri 2 Tukka. This study employed Classroom Action Research (CAR), which was conducted in two cycles, with each cycle consisting of two meetings. Each cycle included four stages: planning, action, observation, and reflection. The subjects of this study were 29 students of Class XI-1 at SMA Negeri 2 Tukka in the 2025/2026 academic year. The results of the study showed that the percentage of students’ learning creativity achievement increased from the pre-cycle to Cycle II. In the pre-cycle stage, 10 out of 29 students achieved mastery learning with a percentage of 34.48%. In Cycle I Meeting I, 12 students achieved mastery learning with a percentage of 43%, which increased to 15 students with a percentage of 52% in Cycle I Meeting II. Furthermore, in Cycle II Meeting I, 18 students achieved mastery learning with a percentage of 62%, and this increased to 24 students with a mastery percentage of 83% in Cycle II Meeting II. Based on these findings, it can be concluded that the implementation of the Everyone Is A Teacher Here (ETH) learning strategy on the topic of Electromagnetic Waves was eff